Best Answer

Subtract 3x from each side: -4 = 2x + 6

Subtract 6 from each side: -10 = 2x

Divide each side by 2: x = -5

Q: 3x - 4 equals 5x plus 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

If: 3x+8-x = 5x-4 Then: x = 4

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

(3, -4)

Related questions

5x - 4 = 3x + 6 5x - 3x = 6 + 4 2x = 10 x = 5

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

If: 3x+8-x = 5x-4 Then: x = 4

5x+2 = 3x-6 5x-3x = -6-2 2x = -8 x = -4

3x + 5x = 348x = 34x = 34/8x = 17/4 orx = 4.25

3x-4=5x+6 gives: 2x=-10 which gives x=-5

6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2

3x + 4 = 5x - 6 -3x -3x 4 = 2x - 6 +6 +6 10 = 2x 5 = x

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5

(3, -4)